Olympiodorus: Life of Plato and On Plato First Alcibiades 1–9 - Griffin, Michael (Bloomsbury Academic, 2014)
This Open Access book looks at Olympiodorus (AD c. 500–570), possibly the last non-Christian teacher of philosophy in Alexandria, who delivered these lectures as an introduction to Plato with a biography. For us, they can serve as an accessible introduction to late Neoplatonism. Olympiodorus locates the First Alcibiades at the start of the curriculum on Plato, because it is about self-knowledge. His pupils are beginners, able to approach the hierarchy of philosophical virtues, like the aristocratic playboy Alcibiades. Alcibiades needs to know himself, at least as an individual with particular actions, before he can reach the virtues of mere civic interaction. As Olympiodorus addresses mainly Christian students, he tells them that the different words they use are often symbols of truths shared between their faiths. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The University of British Columbia.
Keywords: Kommentar; Plato; Olympiodorus; Alcibiades; In Platonis Alcibiadem commentarii; Ethics and moral philosophy; Ancient philosophy; Scholion; Übersetzung; Englisch; Western philosophy: Ancient; to c 500; Ethics & moral philosophy